Biochemical characterization of the small isoform of Drosophila melanogaster RECQ5 helicase - Özsoy, A. Zeynep (Oxford University Press, 2001)
Recently the gene encoding a member of the RecQ helicase family, RecQ5, was cloned from the fruit fly, Drosophila melanogaster [J.J.Sekelsky, M.H.Brodsky, G.M.Rubin and R.S.Hawley (1999) Nucleic Acids Res., 27, 3762–3769]. The Drosophila RecQ5 transcript is alternatively spliced, like its human counterpart, to yield three protein isoforms. Two of these isoforms are almost identical and have a predicted molecular weight of 54 kDa. The third isoform is larger and contains, in addition to the helicase domain shared by all three isoforms, a long highly charged C-terminal region. A small isoform of the Drosophila RecQ5 protein (RECQ5) has been expressed in Escherichia coli and purified. The purified protein is a single-stranded DNA-stimulated ATPase (dATPase) and a 3′→5′ DNA helicase. Hydrolysis of the nucleotide cofactor is required for unwinding activity and dATP supported the unwinding reaction better than other NTPs. The turnover number for the single-stranded DNA-stimulated dATPase activity was 1380 min(–1), ~1.5-fold higher than that observed for the ATPase activity (900 min(–1)). The purified protein catalyzed unwinding of partial duplex substrates up to at least 93 bp, however, unwinding of an 89 bp blunt duplex substrate was not detected.